THE RANGE OF CREATIVE EXPLORATION AND TECHNICAL EXPERIMENTATION IN PRINTMAKING PRACTICES AND IMPORTANCE OF ENVIRONMENTAL CONSERVATION - Pranjit Sarma (Galaxy International Interdisciplinary Research Journal, 2022)
The research paper tried to address the various creative explorations and technical experimentations in contemporary printmaking practice. The chronological development of printmaking techniques and eco-friendly approach has been discussed throughout this paper. Especially, the paper has focused to illustrate the olden eastern block prints and their fundamental purposes. The traditional Indian relief printmaking practice and no-toxic technique of printmaking have also been mentioned in this Paper. After analyzing the western non-toxic printing exploration, invention and practice, the research topic has finally arrived at the conclusion- “The importance of such printmaking practice plays a very major role in productive outcomes in the field of contemporary printmaking Art”.